What's in a home? Toward a critical theory of housing/dwelling. (September 2019) - Handel, Ariel
What is a home/house? How can we bridge between the concepts of a house, as a physical structure, and a home, with its symbolic and human meanings? The paper suggests an outline for a theory of housing/dwelling that considers the multiple facets of homes/houses: a top-down manufactured object, an ideal representation of ontological security, and a site of everyday lives and complex social relations. Combining several philosophical backgrounds—phenomenological dwelling, actor-network theory, Foucault's dispositive, and Illich's vernacularity—the home/house is investigated along three layers: (1) housing regime, that is the home/house as part of a broader system of planning, economy, or national goals; (2) critical phenomenology, aimed at finding and describing the gaps between the ideal-home image characterizing a given society and the home/house's actual behavior; and (3) active dwelling, which regarded this gap as an engine for home-making as a political and agentic process. The theoretical arguments are briefly demonstrated through the case study of Palestinian homes/houses in the Occupied Territories, as political sites of both vulnerability and agency.